Historic Building Information Modelling (hbim): The Application Of Digitalization In Conserving Negeri Sembilan Traditional Malay House - Siti Azira Abd Rahim; Nurul Syala Abd Latip; Nurulhuda Ahamad; Mohd Amir Shazwan Hashim; Farhana Mohd. Zaini; Sangeetha Arjinan; Noor Hayati Ismail (©INTI International University 2022, 2024)
Non-Indexed Publication